Emergence and Utility of Nonspherical Particles in Biomedicine - Fish, Margaret B. (Ind Eng Chem Res, 2015)
The importance of the size of targeted, spherical drug carriers has been previously explored and reviewed. Particle shape has emerged as an equally important parameter in determining the in vivo journey and efficiency of drug carrier systems. Researchers have invented techniques to better control the geometry of particles of many different materials, which have allowed for exploration of the role of particle geometry in the phases of drug delivery. The important biological processes include clearance by the immune system, trafficking to the target tissue, margination to the endothelial surface, interaction with the target cell, and controlled release of a payload. The review of current literature herein supports that particle shape can be altered to improve a system’s targeting efficiency. Non-spherical particles can harness the potential of targeted drug carriers by enhancing targeted site accumulation while simultaneously decreasing side effects and mitigating some limitations faced by spherical carriers.